DESCRIPTION OF THE LARVAE OF NATALIS LA PLACEI LAPORTE, 1836 AND NEO GYPON YX PUNCTIPENNIS (GERMAIN, 1855) (COLEOPTERA: CLERIDAE: CLERINAE) (Acta Entomológica Chilena, 2022)
The larvae of Natalis laplacei Laporte, 1836 and Neogyponyx punctipennis (Germain, 1855), type species of their respective genera, are described. Figures of head, mouthparts and urogomphi and of the habitus of one of the species are provided.
Keywords: Coleóptera, Cleridae, Natalis, Neogyponyx, larval description